Manhaju Ta‘līmi al-Lughah al-‘Arabiyyah fī Daulataini Indūnīsiyyā wa Mālīziyyā - Luthfi Anisatin; Ali Mahmud Asmui (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2023)
This study aimed to determine the differences in curriculum between two countries, namely Indonesia and Malaysia, in their implementation, especially in learning Arabic. In this case, the Arabic curriculum in Indonesia used the 2013 curriculum regulations or known as K13 (Kurikulum 2013), while Malaysia uses KSSR (Kurikulum Standart Sekolah Rendah) and KSSM (Kurikulum Standart Sekolah Menengah) regulations in its implementation. The curriculum is a series of plans to streamline teaching and learning. The Arabic curriculum is a set of Arabic learning plans, objectives, and materials systematically compiled to carry out the learning process properly. This research used a qualitative approach. The research method used is library research. The data used as a source for writing are archives obtained from the ministries of Indonesia and Malaysia. Data collection techniques are obtained from documentation by selecting, searching and analyzing data from the literature or sources related to the problem under study. Based on the study's results, it is known that the presentation of material in the K13 and KSSR/KSSM curricula has differences. In its production, K13 emphasizes more on memorizing Arabic vocabulary and grammatical and morphological abilities. In contrast, the KSSR / KSSM curriculum emphasizes four primary skills: listening, reading, speaking, and writing. This is, of course based on the objectives of each curriculum.